70.5k views
1 vote
Evaluate the expression below for

x= -4
6(x + 15)

User Rtist
by
6.0k points

2 Answers

3 votes

Answer:

66

Explanation:

We know x = -4. To solve, we just need to plug in -4 for x.

6 (-4 + 15) =

6 (11) =

66

User Jomara
by
4.8k points
7 votes

Answer:

66

Explanation:

x= -4

6(x + 15)

Substitute x =-4 into the second equation

6(-4+15)

6(11)

66

User Ali Yar Khan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.